1989
DOI: 10.1002/eji.1830190603
|View full text |Cite
|
Sign up to set email alerts
|

Restricted idiotypic profile of anti‐phosphorylcholine antibodies induced by carrier‐specific helper T cell clones

Abstract: The primary antibody response of C57BL/6 mice to phosphorylcholine (PC) is dominated by immunoglobulins of the T15 idiotype family. Using monoclonal antibodies that define individual idiotopes (Id) of T15, it has been shown that the antibody plaque-forming cells (PFC) arise from heterogeneous population of B cells that may express some but not all T15 Id. In the present study, we tested the ability of antigen (keyhole limpet hemocyanin, KLH)-specific CD4+ T cell clones (Th) to provide help for various T15 B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Anti-idiotypic antibodies were used to analyze ilurepertoire of antibody response to the PC hapten (PC-KLH or PC-ovalbumin) with help provided by various carrier-primed TH populations in viiro. It was found that help from the bulk of splenic T cells stimulated a clonotypic anti-PC response which was very different from that stimulated by TH-cell clones; individual TH clones appeared to provide help for distinct PC-reactive B-cell clones (55)(56)(57). To explain such clonotype-specific help, one can envision that optimal stimulus for B-cell activation and growth reqtiires a balance between the strength of the Ig receptor-mediated signal, which depends on the affinity of germline-encoded sig, and the signals from the helper cells.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-idiotypic antibodies were used to analyze ilurepertoire of antibody response to the PC hapten (PC-KLH or PC-ovalbumin) with help provided by various carrier-primed TH populations in viiro. It was found that help from the bulk of splenic T cells stimulated a clonotypic anti-PC response which was very different from that stimulated by TH-cell clones; individual TH clones appeared to provide help for distinct PC-reactive B-cell clones (55)(56)(57). To explain such clonotype-specific help, one can envision that optimal stimulus for B-cell activation and growth reqtiires a balance between the strength of the Ig receptor-mediated signal, which depends on the affinity of germline-encoded sig, and the signals from the helper cells.…”
Section: Discussionmentioning
confidence: 99%